Doing One’s Best: Becoming a Kinship Caregiver - Kara Vander Linden; Catherine J. Tompkins (Grounded Theory Review: An International Journal, 2020)
A kinship family is one where a family member, other than a biological parent, is primarily responsible for the child. In-depth, unstructured interviews with kinship caregivers and children from 15 kinship families were conducted to gain a thorough understanding of interactions and relationships among kinship family members. Other data sources included notes from monthly kinship care committee meetings, kinship care focus groups, and kinship family support groups. The resulting grounded theory, Doing One’s Best, explains a process of becoming a kinship caregiver and doing what one can regardless of multiple factors that make the situation difficult. Chaos increases as situational, relationship and emotional complexity are exacerbated by occurring together, leading to compounding complexity and the need to engage in behaviors to survive.